2020
DOI: 10.1021/acs.est.0c04869
|View full text |Cite
|
Sign up to set email alerts
|

Per- and Polyfluoroalkyl Substances in Dust Collected from Residential Homes and Fire Stations in North America

Abstract: Over the past few years, human exposure to per- and polyfluoroalkyl substances (PFAS) has garnered increased attention. Research has focused on PFAS exposure via drinking water and diet, and fewer studies have focused on exposure in the indoor environment. To support more research on the latter exposure pathway, we conducted a study to evaluate PFAS in indoor dust. Dust samples from 184 homes in North Carolina and 49 fire stations across the United States and Canada were collected and analyzed for a suite of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 65 publications
6
50
0
Order By: Relevance
“…In fact, the dust samples from fire station living areas in our study all had lower detected median levels, and order(s) of magnitude lower maximum levels, of PFAAs compared to dust collected in living areas of 49 fire stations in the US and Canada (the authors did not measure the same PFAA precursors as we did) (Table S3). 30 Thus, the nonexistent or otherwise rare use of PFAS-containing AFFF by the fire stations in our study may be one reason for the lower PFAA dust levels than the fire stations in that other study, which further motivates shifts towards firefighting products that do not contain any PFAS and that are only used sparingly.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In fact, the dust samples from fire station living areas in our study all had lower detected median levels, and order(s) of magnitude lower maximum levels, of PFAAs compared to dust collected in living areas of 49 fire stations in the US and Canada (the authors did not measure the same PFAA precursors as we did) (Table S3). 30 Thus, the nonexistent or otherwise rare use of PFAS-containing AFFF by the fire stations in our study may be one reason for the lower PFAA dust levels than the fire stations in that other study, which further motivates shifts towards firefighting products that do not contain any PFAS and that are only used sparingly.…”
Section: Discussionmentioning
confidence: 52%
“…For PFAAs, concentrations in the fire station living room dust samples were generally lower than previous studies of dust in U.S. homes or offices, although these environments are not directly comparable (Table S3). 30,47,[64][65][66][67][68][69] Only one living room in this study had carpet, which is an important source of PFAAs indoors. 13,47,67 In addition, those studies did not measure the three most frequently detected chemicals in this study's samples-N-EtFOSAA, 6:2 FtS, and 8:2 FtS-which were found at higher concentrations than in previous European studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] PFASs in indoor dust have been reported by a few studies internationally with a large variety in concentrations ranging from below the detection limit to hundreds of ng/g, or even µg/g. 3,[23][24][25][26][27][28][29] PFASs that were frequently determined at high concentrations in dust are perfluorooctanoic acid (PFOA), perfluorooctane sulfonate (PFOS) and fluorotelomer alcohols (6:2 FTOH, 8:2 FTOH). 2 The large difference between concentrations of PFASs in dust in different regions is associated with their presence in personal consumer products and the usage of household products or materials in addition to discrepancies of dust sampling methods and locations.…”
Section: Per-and Polyfluoroalkyl Substancesmentioning
confidence: 99%
“…4,30 Some of the PFASs in indoor dust data up to 2017 have been summarized in the review by Lucattini et al 3 Notably, more research has been conducted to address the presence of indoor dust and its implications to human exposure to PFAS in recent years. [23][24][25][26][27][28][29] For example, Winkens, et al 23 investigated 65 floor dust samples collected from children's bedrooms in Finland for 62 PFAS analytes. The dust samples were dominated by polyfluoroalkyl phosphoric acid esters and FTOHs while five perfluoroalkyl carboxylic acids and PFOS were detected in more than half of the samples in addition to PFOA median concentration of 5.26 ng/g.…”
Section: Per-and Polyfluoroalkyl Substancesmentioning
confidence: 99%